2016
DOI: 10.1530/eje-15-1018
|View full text |Cite
|
Sign up to set email alerts
|

The effect of GH treatment on serum FGF23 and Klotho in GH-deficient children

Abstract: Background: Normal phosphate homeostasis is essential for normal linear growth. The phosphaturic fibroblast growth factor 23 (FGF23)/Klotho axis is a major regulator of phosphate homeostasis; therefore, an intact FGF23/Klotho axis is important for normal linear growth. On the other hand, GH/IGF1 axis has opposing effects on phosphate homeostasis, but the underline mechanisms remain unclear. Aim: The main objective of this study was to investigate the possible interactions of FGF23 and its co-receptor Klotho, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
9
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 31 publications
(40 reference statements)
5
9
2
Order By: Relevance
“…In agreement with other studies, our study showed that cFGF23 increases after GH therapy [ 25 , 40 ]. However, previous studies also reported an increase in serum phosphate concentrations, which was not observed in the present study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with other studies, our study showed that cFGF23 increases after GH therapy [ 25 , 40 ]. However, previous studies also reported an increase in serum phosphate concentrations, which was not observed in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…These results are in line with previous studies showing that GH therapy increases α-Klotho concentrations in GH deficient, paediatric and adult patients [ 24 , 25 ]. Although the increment of α-Klotho concentrations was more prominent in the small study group of Locher et al.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…PD0325901 administration blocked this pathway completely, and it is of note that addition of GH treatment did not reverse this effect or the elevation of FGF23 serum levels. In agreement with these results, former studies have found a positive correlation between GH and FGF23 levels (32,33), probably mediated by the signal transducer and activator of transcription pathway. However, MAPK i treatment reduced, although did not normalize, circulating FGF23 concentrations even in the Hyp-MAPK i -GH group.…”
Section: Discussionsupporting
confidence: 88%
“…Bone growth requires a positive phosphate balance, and IGF1 indeed elevates serum phosphate concentration by stimulating renal phosphate reabsorption and calcitriol formation (44), which are effects expected to enhance FGF23 production. In line with this, a positive association of IGF1 with FGF23 was observed (45), and an elevation of FGF23 was found in patients with acromegaly (46) and in GH-deficient children treated with recombinant GH (47,48). Therefore, IGF1 may have opposing effects on FGF23: A direct FGF23-lowering effect was demonstrated in our study, limiting the indirect FGF23-stimulating actions of IGF1, which may otherwise counteract its phosphate-retaining effect.…”
Section: Discussionsupporting
confidence: 85%